Gamburtsev subglacial mountains provenance of Permian-Triassic sandstones in the prince charles mountains and offshore prydz Bay:integrated U-Pb and T(DM) ages and host-rock affinity from detrital zircons - Veevers, J. J.; Saeed, Ayesha (Gondwana Research, 2008)
Permian-Triassic drainage radiates from the Gamburtsev Subglacial Mountains (GSM) in central Antarctica. Proximal to the GSM are Permian-Triassic fluvial sandstones in the Prince Charles Mountains (PCM), and neighbouring ?Triassic red beds in Prydz Bay (PB) ODP740A. We analysed detrital zircons for U-Pb ages, Hf-isotope compositions, and trace elements to determine the age, rock-type and source of the host magma, and "crustal" model age (T(DM)(C)). Populations of detrital zircons are (1) 700 to 500 Ma, host magmas granitoid and alkaline rock, T(DM)(C) ranges from 2.5 to 1.1 Ga, and (2) 1200-800 Ma, host magmas mafic granitoid and alkaline rock, T(DM)(C) 2.1 to 1.5 Ga. The bedrock of the PCM-PB region is a potential provenance of the detrital zircons, but the same populations in Permian siltstone south of the PCM and in sediment inclusions in ice at Lake Vostok indicate that the GSM-Vostok Subglacial Highlands (VSH) are the main provenance. Similar detrital zircons in other sandstones in Gondwanaland downslope from a wider central Antarctic reflect an upslope provenance including the GSM-VSH as a complex of 1200-800 Ma (Grenville) and older cratons with mafic granitoids embedded in 700-500 Ma fold belts with granitoids and alkaline rocks. During the past 1000 Ma, the GSM has undergone intermittent uplift on a scale resembling that of the present uplands of Central Asia. (C) 2007 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.